Potensi Air Tanah pasca Gempa Tektonik di Lereng Merapi Daerah Klaten Jawa Tengah - S Suharjo; Alif Noor Anna; Retno Woro Kaeksi; Yuli Priyana (Universitas Muhammadiyah Surakarta, 2008)
The purpose of this research is to analyze the potency of land water in the post tectonic earchquake at Merapi slope in Klaten regency, Central Java. This research applies a survey method. The result of analysis is made based on the trilinier diagram, Stiff pattern, and the quality standard of drinking water. The collected data are in the form of land form, shallow land water data, suppressed land water, and well or spring. The results of the sesearch show that 1) the land form in Klaten is divided into four sets of landform, they are peak and slope of volcano, feet of volcano, fluvial palin under volcano, and a set of structural morphology. 2) The potency of land water can be tested based on the amount of land water and the quality of land water. The amount of land water in Klaten regency 260,502,274 m3/year or 727,618,722 liter/day. The amount of land water above is taken from free land water 73,301,436 m3/year, suppressed land water 34,138,520 m3/year, and land water taken from well or spring 153,062,784 m3/year. The quality of shallow land water in Klaten regency is proper to consume. 3) The distribution of upland water potency happens in the feet volcano land form, the potency of medium land water happens in the superficial of fluvial under volcano land form, and the potency of lowland water happens in the slope volcano land form and in the structural range of hills at Bayat subdistrict, 4) The tectonic earthquake gives serious effect toward morphological changes, land split, land subsident and the potency of land water in the fluvial plain of land form under volcano and structural range of hills in the area of Bayat subdistrict, and 5) In 2008, the needs of drinking water in Klaten regency is predicted around 1,164,000 people x 150 liter/day = 174,600,000 liter/day.